Curiosity and the economics of attention. (October 2020) - Wojtowicz, Zachary; Loewenstein, George
Highlights: Curiosity allocates attention in a way that does not itself consume attention. Hedonic states supplement decision-making with cheap auxiliary appraisals of value. Curiosity homeostatically maintains our ability to make sense of the world. Curiosity internalizes otherwise unappreciated sense-making costs and benefits. Abstract : In this perspective, we propose a functional account of curiosity based on the premise that it evolved to help us efficiently allocate a scarce cognitive resource: attention. This economic perspective clarifies curiosity's place in the pantheon of motivational feeling states by explaining why it shares certain features with both the primary drives (such as hunger, pain, and lust) and other forces that direct cognition (such as boredom, flow, and mental effort). It also provides new insights into domains of interest to both psychologists and economists, such as education, scientific discovery, and self-exposure to news and other sources of information.